Improving Students' Knowledge of HIV/AIDS Prevention at NU 1 Gresik High School Through Health Education - Wibowo, Bima Ardiyanto (Future Science, 2025)
The rise in HIV/AIDS cases among adolescents is a growing public health concern in Indonesia. Limited knowledge regarding HIV/AIDS prevention contributes significantly to risky behaviors among adolescents. This study aimed to improve students’ knowledge of HIV/AIDS prevention at SMA NU 1 Gresik through interactive health education. A quasi-experimental one-group pretest–posttest design was employed using a mixed-method approach. The intervention consisted of interactive counseling through lectures and question-and-answer sessions involving 31 students. Data were collected using pretest and posttest questionnaires. The results showed a significant increase in students' knowledge, from 75.8% in the pretest to 94.4% in the posttest. Students also demonstrated improved understanding of HIV/AIDS transmission, prevention strategies, and risk factors. These findings indicate that interactive health education is effective in enhancing adolescents’ knowledge and awareness regarding HIV/AIDS prevention. Therefore, integrating interactive health education into school-based programs is essential to reduce the risk of HIV/AIDS transmission among adolescents.